2023
DOI: 10.1523/jneurosci.1976-21.2022
|View full text |Cite
|
Sign up to set email alerts
|

Morphology, Connectivity, and Encoding Features of Tactile and Motor Representations of the Fingers in the Human Precentral and Postcentral Gyrus

Abstract: Despite the tight coupling between sensory and motor processing for fine manipulation in humans, it is not yet totally clear which specific properties of the fingers are mapped in the precentral and postcentral gyrus. We used fMRI to compare the morphology, connectivity and encoding of the motor and tactile finger representations (FR) in the precentral and postcentral gyrus of 25 five-fingered participants (8 females). Multivoxel pattern, structural and functional connectivity analyses demonstrated the existen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Crucially, two recent human fMRI studies found that multivariate patterns of neural activity in S1 significantly correlate with the spatial features of the hand and even more so with the spatial features of biased hand perception. 31,32 In this context, these studies suggest that the Bayesian computations that produce geometric finger distortions occur in early somatosensory cortical processing. We hypothesize that the integration of the spatial likelihood and prior is implemented in S1, perhaps through biases in tuning curve distributions 33 and/or neural population dynamics.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Crucially, two recent human fMRI studies found that multivariate patterns of neural activity in S1 significantly correlate with the spatial features of the hand and even more so with the spatial features of biased hand perception. 31,32 In this context, these studies suggest that the Bayesian computations that produce geometric finger distortions occur in early somatosensory cortical processing. We hypothesize that the integration of the spatial likelihood and prior is implemented in S1, perhaps through biases in tuning curve distributions 33 and/or neural population dynamics.…”
Section: Discussionmentioning
confidence: 88%
“…48 Furthermore, two recent human fMRI studies reported that activity in S1 correlates with the spatial features of the hand and biases in hand perception, as if it embeds a spatial prior. 49,50 In neurocomputational terms, this prior may interact with sensory signals by influencing tuning curve distributions, 51 lateral intraareal connectivity strength, 52 and/or neural population dynamics. 53 Another possibility is that the Bayesian computation is more distributed and may include other regions.…”
Section: Discussionmentioning
confidence: 99%
“…The INS is a hub in the SN, which is mainly responsible for regulating attention shifting between the exogenous and endogenous states [ 45 47 ]. The PoCG belongs to the primary sensory cortex (S1) and combines the premotor cortex, primary motor cortex, and posterior parietal cortex to receive and integrate motor and sensory information for planning and coordinating complex movements [ 48 , 49 ]. The TTG also known as Heschl’s gyrus is the typical location of the primary auditory cortex and is the first cortical structure to process incoming auditory information [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The INS is a hub in the SN, which is mainly responsible for regulating attention shifting between the exogenous and endogenous states [45][46][47]. The PoCG belongs to the primary sensory cortex (S1) and combines the premotor cortex, primary motor cortex, and posterior parietal cortex to receive and integrate motor and sensory information for planning and coordinating complex movements [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…The latero-medial organization from the thumb to the little finger in somatosensory cortex was originally observed by Penfield using intraoperative electrical stimulation of humans 24,25 and has been confirmed in multiple species [26][27][28][29][30] including non-human primates [18][19][20]31 . This somatotopic finger organization can also be observed in humans using non-invasive imaging techniques -functional magnetic resonance imaging (fMRI) and magnetoencephalography (MEG) [32][33][34][35][36][37][38][39][40] . Importantly, several studies have demonstrated highly preserved finger representations in people who were deafferented through amputation [41][42][43][44] or spinal-cord injury (SCI) 45 ; the two groups of people most likely to benefit from BCIs to restore upper limb function.…”
Section: Introductionmentioning
confidence: 91%